Assessment of Consumption Pattern of Fuelwood and Fodder Species in Chamba Block, Tehri Garhwal, Uttarakhand - Barthwal, Priya; Bali, Rajender Singh; Dobhal, Sneha; Lal, Pankaj; Thakur, Sakshi; Thakur, Priyanka; Negi, Saumya (International Journal of Economic Plants, 2026)
The study was conducted during 2023–2024 in nine villages of the Chamba block, Tehri Garhwal district, Uttarakhand, to assess seasonal patterns of fuelwood and fodder consumption and the associated socio-economic characteristics of rural households. A participatory rural appraisal approach was adopted. A total of 135 households were selected through stratified random sampling, and primary data were collected using semi-structured questionnaires, household surveys, and direct field measurements. Fuelwood consumption was estimated using a 24-hour weight-survey method, while fodder consumption was quantified based on livestock numbers standardized to cattle equivalent units. The results indicated a predominance of nuclear families (80%) and an ageing population, with agriculture remaining the primary occupation. Fuelwood was identified as the principal household energy source across all villages. Per capita fuelwood consumption increased from 1.67 kg day-1 in summer to 2.59 kg day-1 in winter. Fodder consumption showed seasonal variation, with a mean intake of 16.65 kg day-1 cattle-1 in summer and 15.36 kg day-1 in winter, largely derived from forest vegetation and multipurpose tree species. Fuelwood and fodder collection required substantial labour input, long travel distances, and significant time investment. The findings indicated strong seasonal dependence on forest resources and highlighted the need for sustainable biomass management and agroforestry-based fodder development.